Profil Kemampuan Technological Pedagogical Content Knowledge (TPACK) Guru pada Pembelajaran Matematika - Nurwati Djam'an; Fajar Arwadi; Adsyira Almukitra (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study aims to examine the profile of teachers’ Technological Pedagogical Content Knowledge (TPACK) in mathematics instruction. The type of research employed is qualitative with a descriptive approach. The research subjects consisted of two Grade VIII mathematics teachers at UPT SMPN 2 Takalar. The instruments used for data collection included a self-assessment questionnaire, observation sheets, field notes, and interview guidelines. The data analysis techniques consisted of: (1) data organization, (2) data presentation, and (3) conclusion drawing. Data validity was ensured through source and technique triangulation. The results of the study indicate that the mathematics teachers’ TPACK is at a very good level, particularly in the areas of developing teaching modules, assessment, classroom management, selecting appropriate technology or instructional media, mastering subject matter, and integrating technological, pedagogical, and content aspects. However, in terms of implementation, several areas need improvement. These include deficiencies in the components of the teaching modules, teaching practices that are not fully aligned with the prepared modules, and instructional methods and strategies that have not been fully optimized to support the effectiveness of learning and students' understanding of statistical content. The process of guiding discussions and question-and-answer sessions needs to be further optimized to encourage more active student participation and promote independent understanding. While the teachers have demonstrated the ability to use technological, pedagogical, and content knowledge separately, there is still a need to enhance the integration of all three components simultaneously in the learning process.